Early microvascular changes in the preterm neonate: a comparative study of the human and guinea pig. Issue 9 (17th September 2014) - Dyson, Rebecca M.; Palliser, Hannah K.; Lakkundi, Anil; de Waal, Koert; Latter, Joanna L.; Clifton, Vicki L.; Wright, Ian M. R.
Abstract Dysfunction of the transition from fetal to neonatal circulatory systems may be a major contributor to poor outcome following preterm birth. Evidence exists in the human for both a period of low flow between 5 and 11 h and a later period of increased flow, suggesting a hypoperfusion–reperfusion cycle over the first 24 h following birth. Little is known about the regulation of peripheral blood flow during this time. The aim of this study was to conduct a comparative study between the human and guinea pig to characterize peripheral microvascular behavior during circulatory transition. Very preterm (≤28 weeks GA), preterm (29–36 weeks GA), and term (≥37 weeks GA) human neonates underwent laser Doppler analysis of skin microvascular blood flow at 6 and 24 h from birth. Guinea pig neonates were delivered prematurely (62 day GA) or at term (68–71 day GA) and laser Doppler analysis of skin microvascular blood flow was assessed every 2 h from birth. In human preterm neonates, there is a period of high microvascular flow at 24 h after birth. No period of low flow was observed at 6 h. In preterm animals, microvascular flow increased after birth, reaching a peak at 10 h postnatal age. Blood flow then steadily decreased, returning to delivery levels by 24 h. Preterm birth was associated with higher baseline microvascular flow throughout the study period in both human and guinea pig neonates. The findings do not support a hypoperfusion–reperfusion cycle in the microcirculation during circulatory transition. The guinea pig model of preterm birth will allow further investigation of the mechanisms underlying microvascular function and dysfunction during the initial extrauterine period.